Identification of Tourism Village Communication Potential in The New Normal Era in Semarang Regency - Septemuryantoro, Syaiful Ade (Media Wisata, 2024)
Generating the potential of tourist villages during the pandemic is an alternative way of reviving post-covid-19. The potential of human resources and natural resources must be mapped and communicated.Semarang Regency has the potential of natural resource wealth.This study aims to determine the communication potential of tourist villages in Semarang Regency during the pandemic.Implementing local-based community empowerment in Semarang Regency. Qualitative descriptive research method with data collection through interviews.This study uses a SWOT analysis as a way to determine the potential of a tourist village.The results of the study indicate the background of increasing local-based potential empowerment in the implementation of tourism village management.